Do Elections Always Motivate Incumbents? : Experimentation vs. Career Concerns - Lockwood, Ben (IMF Working Papers; Working Paper ;, 2003)
This paper studies a principal-agent model of the relationship between an incumbent officeholder and the electorate, where the officeholder is initially uninformed about her ability. If officeholder effort and ability interact in the "production function" that determines performance in office, then an officeholder has an incentive to experiment-that is, raise effort so that performance becomes a more accurate signal of her ability. Elections reduce the experimentation effect, and the reduction in this effect may more than offset the positive "career-concerns" effect of elections on effort. Moreover, when this occurs, appointment of officeholders may Pareto-dominate elections.